Design information systems for the management and inventory of goods with web-based a priori algorithm methods - Jenni Sabarina Br Sitepu; Verdi Yasin; Akmal Budi Yulianto (Yayasan Bina Internusa Mabarindo, 2022)
This study uses data collection methods by means of observation, interviews, and literature study, namely by making direct observations on the object under study and asking for the necessary data, as well as interviews or questions and answers to the resource person to complete the data and obtain the necessary information. The author raises the issue of the absence of a special program to store data and make reports in the Warehouse Section at PT. Creative Clothing Creations Branch. The company also manages incoming goods data, outgoing goods data, returned goods data, calculated in the inventory data. This activity is very important, increases efficiency, and determines its performance in terms of inventory cost savings. Previously, data processing was done in a conventional way, using Microsoft Excel and Word. By designing a computerized system using PHP and MySql applications, goods data and supplier data can be stored in a database to facilitate daily transactions in the warehouse. This system was created to be able to manage inventory data, goods receipt transactions, goods expenditure transactions and reports. The designed information system is expected to minimize the shortcomings of the data collection and recording system that has been used so far so that work activities are more controlled.